Mechanistic effect of the human GJB6 gene and its mutations in HaCaT cell proliferation and apoptosis - Yuting Lu (Brazilian Journal of Medical and Biological Research, 2018)
We constructed lentiviral vectors containing the human wild-type GJB6 gene and the mutant variants A88V and G11R. The three proteins were stably expressed by the Tet-on system in the HaCaT cell line and used to study the functional effect of the variants. The CCK-8 assay and flow cytometric analyses were used to determine the levels of cell proliferation and apoptosis. Western blot analyses were performed to analyze the relevant clinical indicators of hidrotic ectodermal dysplasia and markers of apoptosis in transfected HaCaT cells. The CCK8 assay and the flow cytometry results showed a significant increase (P<0.05) in the apoptosis of HaCaT cells expressing the A88V and G11R mutants. In addition, we demonstrated that the A88V and G11R mutants induced the apoptosis of transfected HaCaT cells via the activation of caspase-3, -8, -9, and PARA. No change was observed in the activity of BAX compared with the control. This study provides further clarification on the mechanisms underlying the effect of the mutant variants A88V and G11R of the GJB6 gene on the induction of HaCaT cell apoptosis.